Solutions for the Legality of Child Legal Actions in Making of the Notary Deed and PPAT Deed - Asep Hermawan (Sultan Agung Notary Law Review, 2020)
This study aims to analyze and assess the legal arrangements for legal acts of children in the practice of notary duties and positions in the perspective of the Notary Position Law, as well as obstacles and solutions to its implementation. This study used a sociological juridical approach with descriptive analysis characteristics. Sources of data used in this study include primary data taken using interviews and secondary data with documentation studies, data analyzed using qualitative descriptive. Based on the research, it is concluded that the legal actions of a new child can be declared valid if the child is 18 years old, but in practice, notaries only serve the making of notary deeds for those who are 18 years old, while PPAT deed services are only intended for those who are 21 years old. The difference in service is the difference in age because of the existenceRegulation of the Head of the National Land Agency which enforces a minimum age of 21 years for PPAT deeds, according to the provisions of the Civil Code (BW). The Regulation of the Head of BPN is an obstacle to the application of UUJN and even makes UUJN have no legal certainty, it is also against the constitution and other laws of a higher degree. As a solution, the notary divides the deed into two parts, namely the notary makes a deed for 18 years old in the form of a notary deed, and for those who are 21 years old, besides a notary deed, a PPAT deed can also be made.